Growth Enhancement Facilitated by Gaseous CO2 through Heterologous Expression of Reductive Tricarboxylic Acid Cycle Genes in Escherichia coli - Shou-Chen Lo (Fermentation, 2021)
The enzymatic mechanisms of carbon fixation by autotrophs, such as the reductive tricarboxylic acid cycle (rTCA), have inspired biotechnological approaches to producing bio-based chemicals directly through CO2. To explore the possibility of constructing an rTCA cycle in Escherichia coli and to investigate their potential for CO2 assimilation, a total of ten genes encoding the key rTCA cycle enzymes, including α-ketoglutarate:ferredoxin oxidoreductase, ATP-dependent citrate lyase, and fumarate reductase/succinate dehydrogenase, were cloned into E. coli. The transgenic E. coli strain exhibited enhanced growth and the ability to assimilate external inorganic carbon with a gaseous CO2 supply. Further experiments conducted in sugar-free medium containing hydrogen as the electron donor and dimethyl sulfoxide (DMSO) as the electron acceptor proved that the strain is able to undergo anaerobic respiration, using CO2 as the major carbon source. The transgenic stain demonstrated CO2-enhanced growth, whereas the genes involved in chemotaxis, flagellar assembly, and acid-resistance were upregulated under the anaerobic respiration. Furthermore, metabolomic analysis demonstrated that the total concentrations of ATP, ADP, and AMP in the transgenic strain were higher than those in the vector control strain and these results coincided with the enhanced growth. Our approach offers a novel strategy to engineer E. coli for assimilating external gaseous CO2.